Resistencia antimicrobiana: bacterias inmunes a nuestras armas. - Ortiz Rivera, Yuridia (2022)
https://www.revistaciencia.amc.edu.mx/index.php/ediciones-anteriores/edicion-actual/334-novedades-cientificas/981-resistencia-antimicrobiana-bacterias-inmunes-a-nuestras-armas